(untitled) (Journal of Vishwa Adarsha College, 2024)
This article explores the Nepali epic Agni by Nawaraj Lamsal through its proletariat character, ‘Thule Kami’. Using Marxism as its theoretical framing, it analyzes how the existing Nepali society experiences class struggle and how economic power serves as a political power to suppress the powerless people. The article further presents how poverty-stricken people struggle for their livelihood against the socio-economic condition of Nepali society. It brings to light how the rulers and power mongers of society first use and later discard the lower-class people like Thule Kami to fulfill their vested interests. Drawn on the life of the protagonist, it reveals not only the poor economic conditions and exploitation faced by the proletariat but also their evolving consciousness of the need to protest.